bell hooks : the last interview and other conversations - Zylan, Yvonne; Tworkov, Helen; Chua, Lawrence; Miya-Jervis, Lisa; Jennings, Don; House, Silas, 1971-; Bereola, Abigail (Last interview series., 2023)
"bell hooks was a prolific, trailblazing author, feminist, social activist, cultural critic, and professor. Born Gloria Jean Watkins, bell used her pen name to center attention on her ideas and to honor her courageous great-grandmother, Bell Blair Hooks. hooks's unflinching dedication to her work carved deep grooves for the feminist and anti-racist movements. In this collection of 7 interviews, stretching from early in her career until her last interview, she discusses feminism, the complexity of rap music and masculinity, her relationship to Buddhism, the "politic of domination," sexuality, and love and the importance of communication across cultural borders. Whether she was sparking controversy on campuses or facing criticism from contemporaries, hooks relentlessly challenged herself and those around her, inserted herself into the tensions of the cultural moment, and anchored herself with love"--